Toxicity of Metals and Metallic Nanoparticles on Nutritional Properties of Microalgae - Liang, Sharolynne, Xiao Tong; Wong*, Ling Shing; Tanislaus, Anto Cordelia; Dhanapal, Antony; Sinouvassane, Djearamane (Springer, 2020)
Microalgae has been utilized as food and supplement by humans for more than thousands of years due to their high nutritional properties such as proteins, vitamins, minerals, and other nutrients. However, the improvement in the modern society caused increased release of metals and metallic nanoparticles (MNPs) into the freshwater that might cause toxicity to the marine and freshwater microalgae. Although low concentration of these metals and MNPs will not affect the metabolism of microalgae, high concentration of metals and MNPs, on the other hand, can cause toxicity to microalgae. Studies have been done to evaluate the toxicity mechanism of metals and MNPs and the effect of these metals and MNPs on the nutritional value of microalgae. In this paper, the toxicity mechanism of metals and MNPs to microalgae is highlighted. The effect of the metals and MNPs on the growth rate and nutritional properties (pigments, biological macromolecules, and phenolic compounds) of microalgae are summarized as well.